Hepatobiliary scintigraphy in the study of complications in adult patients after liver transplant. Description of the experience (2019)
Objective: To show the experience of the use of hepatobiliary scintigraphy in patients with suspected complications after liver transplantation in a high complexity centre. Material and method: Retrospective, observational and descriptive study. All consecutive adult patients with liver transplantation between January 2013 and February 2018 were included, with one or more hepatobiliary scintigraphy during the early or late postoperative period. A total of 58 studies were analyzed in 38 patients (22 men and 16 women). Mean age: 48 years. In 34/38: cadaverous donor (89%), and in 4 (11%): a living donor. Demographic data and relevant information regarding the transplant were obtained, and the result was related to the surgical findings to determine the correlation between them. The influence of the test on the final clinical decisions was evaluated. Results: Findings: 9 scans (14%) were normal, 36 studies were negative, and 21 were positive for biliary complications. Of the total of 58 studies, 50 (86%) had impact on the clinical behaviour of observation or intervention. All the patients with findings of biliary complications (21/21; 100%) had clinical repercussion since 18/21 patients were taken to invasive studies or treatments, and 3/21 patients continued in medical management for findings of non-surgical biliary complications. In 14/18 patients taken to studies or procedures, correlation was found with the scintigraphic study. In 24/36 (66%) of patients with negative scintigraphy, an impact on clinical behaviour was found. Conclusion: Hepatobiliary scintigraphy is a simple, non-invasive, reliable, current and available form for the early study of biliary complications in patients with liver transplantation. Important hepatocellular dysfunction should be taken into account as a frequent cause of false negative studies. © 2019 Sociedad Española de Medicina Nuclear e Imagen Molecular